Cumulative long-term recurrence of diabetic foot ulcers in two cohorts from centres in Germany and the Czech Republic. (February 2021) - Ogurtsova, Katherine; Morbach, Stephan; Haastert, Burkhard; Dubský, Michal; Rümenapf, Gerhard; Ziegler, Dan; Jirkovska, Alexandra; Icks, Andrea
Abstract: Aims: Our aim was to comprehensively estimate the incidence of diabetic foot ulcer (DFU) recurrence and corresponding risk factors in two cohorts. Methods: Prospective data from patients with active DFU from two diabetes centres in Germany (GER, n = 222) and the Czech Republic (CZ, n = 99) were analysed. Crude cumulative incidences were obtained. Additionally, time to recurrence and risk factors were investigated using multivariate Cox models. Results: 69%(154) of patients in GER and 70%(69) in CZ experienced at least one DFU recurrence; 25%(56) in DEU and 15%(15) in CZ died; 5%(11) and 9%(9) were lost to follow-up. The crude cumulative incidence in the first year was 28% in GER and 25% in CZ; 68%/70% within ten years, and 69%/70% in 15 years. In GER, renal replacement therapy was associated with shorter time to recurrence (HR = 3.71, 95%CI:1.26–10.87); no history of DFU before the index lesion with longer time to recurrence (HR = 0.62, 0.42–0.92). In CZ, type 2 diabetes (HR = 2.57, 1.18–5.62) and index ulcer treatment by minor amputation (HR = 2.11, 1.03–4.33) were associated with shorter time to recurrence. Conclusions: Cumulative DFU recurrence was approximately 70% in 15 years in both cohorts. We found a significantly higher risk of future recurrence in patients having a consecutive ulcer compared with the first ever ulcer.